LARANGAN PENGASINGAN TANAH DALAM HUKUM ADAT PERSPEKTIF HUKUM AGRARIA NASIONAL - I Made Suwitra (JURNAL YUSTIKA: MEDIA HUKUM DAN KEADILAN, 2018)
Adat Lands as a communal lands nowadays are helds individually. Adat lands in the forms of "Pekarangan Desa" or "Ayahan Desa" actually have Religious-Communalistic Characteristic. These kinds of Adat Lands is sticked with "Ayahan" as an individual obligation of the holders as dedication to their Adat Villages. Recently some of those Adat Lands has been converted into fully individual's land according to the Law Number 5 of 1960. It affected these land has no Religious-Communalistic characteristic anymore, but only has social function in the secular concept. Nowadays, the exiles of adat lands in some Adat Villages in Bali could not avoided potentially emerging conflict. There is no clear understanding of the meaning of "holding process", "holder" and "exiles" which understood as the subject of the rights context, not to the status of the land's context.